Socio economic impacts and policy of artisanal small-scale gold mining in relation to sustainable agriculture: a case study at Sekotong of West Lombok - S Suhartini; A Abubakar (Journal of Degraded and Mining Lands Management, 2017)
Artisanal and small scale gold mining (ASGM) activities at Sekotong Sub District, West Lombok District, West Nusa Tenggara which use a traditional system have been operating since 2008. The objectives of this study were to analyze the socio-economic impacts of ASGM,  to know the policy on ASGM in West Lombok Regency, and to  formulate the policy recommendations of sustainable agricultural management which consider the ASGM activities. This study was conducted at Batu Putih and Pelangan villages of the Sekotong sub District which was chosen purposively. The research method was a case study with survey by interviewing 30 farmers with miners that were selected by a simple random sampling and field observation. A policy study was also used by interviewing key informants from many stakeholders. The results showed that ASGM activities at Sekotong improved the income of farmers/miners and created job opportunities. From the average, the ASGM mining contributed 76.01 % of farmers/miners income,  while the farming incomes was 23.99 % of total income. In 2011, West Lombok local government issued a regional regulation through a decree number 1102A/480A/Distamben/2011 about The Determination of the Artisanal Mining Area. But, after the Law of Republic Indonesia Number 23/2014 on Regional Government, the authority to give the artisanal mining permit is the Provincial Government. In terms of economics, the ASGM activities supported the agricultural sustainability. However, the environmental impact of it activities needs to be addressed with technologies which are economically viable and environtmentally sound such as phytoremediation